2000
DOI: 10.1111/j.1151-2916.2000.tb01505.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Tensile and Compressive Creep Behavior in Silicon Nitride

Abstract: The creep behavior of a commercial grade of Si 3 N 4 was studied at 1350°and 1400°C. Stresses ranged from 10 to 200 MPa in tension and from 30 to 300 MPa in compression. In tension, the creep rate increased linearly with stress at low stresses and exponentially at high stresses. By contrast, the creep rate in compression increased linearly with stress over the entire stress range. Although compressive and tensile data exhibited an Arrhenius dependence on temperature, the activation energies for creep in tensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 22 publications
3
37
1
3
Order By: Relevance
“…Como ejemplo, la figura 2 muestra este hecho en materiales a base de nitruro de silicio, deformados en compresión y en tracción (7,(15)(16)(17); un comportamiento análogo ha sido identificado en cerámicos a base de SiC (18) o de Al 2 O 3 (19) con fases secundarias. En cambio, los materiales monofásicos exhiben el mismo comportamiento en compresión y en tracción (14).…”
Section: Características De La Fluencia De Estos Materialesunclassified
See 1 more Smart Citation
“…Como ejemplo, la figura 2 muestra este hecho en materiales a base de nitruro de silicio, deformados en compresión y en tracción (7,(15)(16)(17); un comportamiento análogo ha sido identificado en cerámicos a base de SiC (18) o de Al 2 O 3 (19) con fases secundarias. En cambio, los materiales monofásicos exhiben el mismo comportamiento en compresión y en tracción (14).…”
Section: Características De La Fluencia De Estos Materialesunclassified
“…Así, la mayor parte de los estudios atribuyen la fluencia en compresión del nitruro de silicio al deslizamiento de fronteras de grano acomodado por disolución-precipitación, si bien existen menciones a acomodación por fluencia viscosa (7). En tracción, en cambio, la deformación se produce generalmente por cavitación acomodado por el deslizamiento relativo de los granos (7,16,17) o por un mecanismo combinado (7,21). Esta afirmación está apoyada por la observación sistemática de que la fracción volumétrica de cavidades aumenta linealmente con la deformación (7,(15)(16)(17)20).…”
Section: Cerámicas No Oxídicas: Si 3 Nunclassified
“…Observation of the microstructure showed that, unlike compression, creep in tension is controlled by cavity formation. At 1.8% strain, the volume fraction of cavities in compression was only 18% of that in tension [10]. In general, polycrystalline materials with a viscous grain boundary phase exhibit larger creep strains in tension compared to compression [11].…”
Section: mentioning
confidence: 99%
“…For example, silicon nitride was subjected to compressive and tensile creep stresses ranging between 10 and 300 MPa at temperatures between 1350 and 1400 ℃ [10]. Over the entire stress range, compressive creep rates showed a linear dependence with stress.…”
Section: mentioning
confidence: 99%
“…La fluencia de estos compuestos en compresión y en tracción ha sido investigada en un gran número de estudios (1)(2)(3)(4)(5), que han puesto de manifiesto que la fluencia estacionaria del nitruro de silicio está controlada por cavitación en tracción (6) y por disolución -reprecipitación en compresión (7).…”
Section: Introductionunclassified